POLITICAL WILL PEMERINTAH KABUPATEN PELALAWAN TERHADAP PELESTARIAN SATWA DI TAMAN NASIONAL TESSO NILO TAHUN 2011-2012 - Achmad Fauzy; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study purpose to determine whether there is political will Pelalawan Government Against Wildlife Preservation in Tesso Nilo in 2011-2012. The main problem in this research is how the Political Will of Government Pelalawan Against Wildlife Animals in Tesso Nilo in 2011-2012. How Government Pelalawan willing to take an active role in efforts to Wildlife Animals in Tesso Nilo in 2011-2012.This study is a qualitative research using descriptive analysis method. This study used an interview with the informant as the object information that aims to achieve the goal in order to obtain the information in the study. The type of data used in this research is primary data and secondary data with obtained and interviews with informants in this study.Based on the results, it can be concluded that the political will of the Government Pelalawan wildlife conservation in TNNP in 2011-2012 is still lacking even hardly. Theres indicator writers use as a reference to find the political will of the Government of Pelalawan on wildlife conservation in TNNP in 2011-2012, initiatives, priorities, support of mobilitation politic, law enforcement and business continuity. Where all of this indicator did not find the government researchers Pelalawan on wildlife conservation in TNNP in 2011-2012.Based on the results of the study also found some inhibiting factors in wildlife conservation efforts in TNNP among others, lack of political will Pelalawan District Government, lack of awareness of all parties that animals have a right to life, lack of support or support from the local community and the security area is still not maximum.Keywords: Political will, Tesso Nilo National Park, indicators of political will